A matemática financeira como instrumento da educação financeira - MODESTO, Gabriel Ferreira Favacho (2024)
Throughout life, people are faced with various financial decisions, from the simplest to the most complex. This basic knowledge needed to handle simple financial tasks is known as financial literacy. Many individuals have a low level of financial education, which ends up making it difficult to make healthy decisions and makes them more prone to debt. The objective of this study is to analyze the relationship between the practice of financial education and debt. To make decisions appropriately, it is important to have a previously prepared budget that includes forecasts of income and expenses. This helps in managing finances and is an effective tool for disciplining financial habits. In this way, financial education aims to improve people's understanding of how to manage their money, seeking conscious and healthy use. Its purpose is to guide decision-making, offering skills that citizens develop throughout their lives to make conscious choices regarding their finances and plan the best way to manage their money.